Life cycle greenhouse gas emissions and energy use of polylactic acid, bio-derived polyethylene, and fossil-derived polyethylene. (20th December 2020) - Benavides, Pahola Thathiana; Lee, Uisung; Zarè-Mehrjerdi, Omid
Abstract: Bioplastics recently have become an attractive, viable, and popular alternative to conventional petroleum-based plastics, with the hope that replacing fossil-derived plastics with renewable alternatives will reduce greenhouse gas (GHG) emissions and fossil energy consumption (FEC). The bioplastic industry is encouraging creative designs and enhanced properties such as biodegradability, which is considered a sustainable solution for waste plastic management. However, biodegradability also means that carbon in the product is emitted to the atmosphere as GHG emissions. In this paper, a life cycle analysis (LCA) of biodegradable polylactic acid (PLA) and bio-polyethylene (bio-PE) plastics was conducted to understand the environmental effects of these bioplastics from feedstock production to product end-of-life (EOL). In particular, emissions from biodegradability (EOL emissions) are accounted for. The results were compared to those of conventional fossil-based plastics such as high-density polyethylene (HDPE) and low-density polyethylene (LDPE). Results showed that the lowest GHG emissions (−1.0 and 1.7 kg CO2 e per kg for bio-PE and PLA with no biodegradation, respectively) and FEC (29 and 46 MJ per kg of bio-PE and PLA, respectively) were achieved with bio-derived plastics, particularly bio-PE plastic. However, despite the benefits of biogenic carbon uptake, when landfill and composting emissions were considered for the PLA pathway, the life cycle emissions of PLA increase significantly, from 16% to 163% depending on the biodegradation condition, compared to the case where there is no degradation in the landfill. This study also contributed to understand the effects on the GHG emissions of biodegradability in landfill and composting scenarios, regional electricity mix, and plastics manufacturing technologies. Highlights: Bioderived PE can offer lower GHG emissions and FEC than the fossil-based counterparts. Biodegradability can greatly influence GHG emissions of bioplastics designed to degrade in landfills or composting. Landfill and composting conditions of PLA determine biodegradability rates. Renewable electricity will improve GHG emissions of PLA production. Less energy-intensive processing methods will benefit the GHG emissions of the plastic pathways.